Structural Performance of Experimentally Investigated CFRP-Strengthened Cold-formed Steel Built-Up Columns - Chakravarthy N.; Naganathan S.; Kalavagunta S.; Mustapha K.N.B. (Springer Science and Business Media Deutschland GmbH, 2023)
This paperpresents the investigation on built-up cold-formed steel column sections strengthened withcarbon fibre-reinforced polymer(CFRP). Here, box-shaped column sections were fabricated by screwing together with individual channels. Behaviour of twelve plain and twelve CFRP-strengthened box sections was studied under axial compression. Three lengths of 300mm, 500mm and 700mm with section thickness of 0.6mm, 0.75mm and 1mmwere studied in the investigation. The cold-formed steel design procedure suggested by North American specification AISI S100-16 and Euro code 3 (EC3) provisions wasapplied and compared with the experimental results, which were in good agreement. The resultsalso indicate that the proposed strengthening technique iseffectivein repair and increasing the load-carrying capacity ofcold-formed steel built-up box column. 2021, Shiraz University.